Influence of Religiosity and Attitude Towards Intention to Purchase Counterfeit Products. An Empirical Study in Dhaka, Bangladesh - Maliha Jashim, Mis; Singh Kartar Singh, Jugindar; Chan Yin-Fah, Benjamin (International Journal of Psychosocial Rehabilitation, 2020)
Counterfeit products represented up to 2.5% of world commerce and valued as much as $461 billion. In Bangladesh, over 50% of cosmetic products were reported as counterfeit. Several past studies have studied the factors that influence consumers’ intention to purchase counterfeit products. However, there is a dearth of research related to the influence of religiosity and attitude towards consumers’ intention to purchase in Bangladesh. In view of this gap, the aim of this study was to find out the influence of religiosity and attitude towards purchasing intention of counterfeits. This was a quantitative study that used a survey method. Primary data was collected using self-administered questionnaires from 165 respondents in Dhaka. The data was analyzed using SPSS version 20. The results of this study revealed that only consumers’ attitude had a significant impact on purchasing intention. The result of this study has implications on policymakers and marketers of counterfeit products. To counter the purchase intention, policymakers need to focus on changing the attitude of consumers. This was a new study in Bangladesh which will add to the body of knowledge.